Human auditory development - Fay, Richard R.; Popper, Arthur N.; Werner, Lynne (Springer Handbook of Auditory Research, 2012)
Human Auditory Development deals with what is currently known about the development of hearing and the auditory system in humans.  This volume provides an important contemporary reference on hearing development and leads to new ways of thinking about hearing in children and about remediation for children with hearing loss.  Much of the material in this volume  documents that a different model of hearing is needed to understand hearing during development. Overview and Issues in Human Auditory Development Lynne A. Werner Morphological and Functional Ear Development Carolina Abdala and Douglas H. Keefe Morphological and Functional Development of the Auditory Nervous System Jos J. Eggermont and Jean K. Moore Development of Auditory Coding as Reflected in Psychophysical Performance Emily Buss, Joseph W. Hall III, and John H. Grose Development of Auditory Scene Analysis and Auditory Attention Lori J. Leibold Development of Binaural and Spatial Hearing Ruth Y. Litovsky Development of Speech Perception Robin Panneton and Rochelle Newman Development of Pitch and Music Perception Laurel J. Trainor and Andrea Unrau Atypical Auditory Development and Effects of Experience Laurie S. Eisenberg, Karen C. Johnson, Sophie E. Ambrose, and Amy S. Martinez About the Editors: Lynne  A. Werner is Professor in the Department of Speech & Hearing Sciences at the University of Washington, Seattle. Richard R. Fay is Professor Emeritus in the Department of Psychology at Loyola University Chicago. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. About the Series:   The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field